Upaya Menggiatkan Sedekah di Era Covid-19: Studi Hadis - Muhammad Sakti Budimansyah; Ilim Abdul Halim; Abdul Syukur (UIN Sunan Gunung Djati Bandung, 2022)
This research was conducted to discuss the hadith about alms. This study uses a qualitative approach by applying a descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith related to alms, namely the hadith in Muslim history no. 1677. The results of this study prove that the status of the hadith studied is of authentic quality and of course meets the qualifications of maqbul ma'mul bih that is accepted and can be used as evidence or evidence for the practice of Islam. This study concludes that the hadith narrated by Muslim No. 1677 is very relevant to be used as motivation and spirit for the practice of alms in daily life, especially in the Covid-19 era that hit Indonesia.